PENGARUH CUSTOMER EXPERIENCE, BRAND CREDIBILITY, DAN BRAND TRUST TERHADAP BRAND LOYALTY YAKULT DI KOTA BATAM - Deviana Zhou; Suhardi Suhardi (LPPM Universitas Putera Batam, 2026)
This study aims to examine the effect of Customer Experience, Brand Credibility, and Brand Trust on Brand Loyalty among Yakult consumers in Batam City. The research uses a quantitative approach with a descriptive research design. Data were collected through a structured questionnaire distributed to 204 respondents who had purchased Yakult products in Batam City. The sampling technique was determined using the Jacob Cohen formula. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results of the partial test (t-test) show that Customer Experience and Brand Trust have a positive and significant effect on Brand Loyalty, while Brand Credibility does not have a significant effect when tested individually. However, the simultaneous test (F-test) indicates that Customer Experience, Brand Credibility, and Brand Trust together have a positive and significant influence on Brand Loyalty. This result suggests that although Brand Credibility does not significantly affect Brand Loyalty on its own, it still plays a role within the overall regression model when combined with other variables. The findings indicate that enhancing customer experience and strengthening brand trust are key strategies in increasing brand loyalty. This study is expected to provide valuable insights for companies, particularly PT Yakult Indonesia Persada, in developing effective marketing strategies to improve and maintain consumer loyalty.